Kepuasan Masyarakat Terhadap Pelayanan Rumah Sakit Rujukan di Provinsi Kepulauan Riau Tahun 2019 - Kiki Rizki Dasaryandi; Yulastri Arif; Eka Roza Wijaya (Universitas Andalas, 2019)
Patient satisfaction is one indicator of quality health services. This study aims to analyze and compares the index patient satisfaction with three hospital services in Riau Islands Province. There was three government hospital compared, namely: District; General; and Otorita Batam hospital. This study used a quantitative approach, with the number of respondents as samples were 762 patients with accidental sampling technique. The data collection used Public Satisfaction Index questionnaire issued by the Indonesian government. The results showed that two government hospital (District and General Hospital) had a high performance in term of hospital services. Meanwhile, even Otorita Batam Hospital has a low performance for the services, public satisfaction index toward the hospital is still high. The condition happened because, in Otorita Batam Hospital, most of the patients in the Batam city were welcome. Most of the patients would consider, they should have their health concerns well response, instead of the facilities or competencies of the health professionals. However, in improving the hospital service performance, some efforts regarding the competency, specific services, and pricing and tariffs are still needed to improve.